Identification and molecular docking studies for novel inverse agonists of SREB, super conserved receptor expressed in brain. (17th May 2016) - Yanai, Toshihiro; Kurosawa, Aya; Nikaido, Yoshiaki; Nakajima, Nozomi; Saito, Tamio; Osada, Hiroyuki; Konno, Ayumu; Hirai, Hirokazu; Takeda, Shigeki
Abstract : The identification of novel synthetic ligands for G protein‐coupled receptors (GPCRs) is important not only for understanding human physiology, but also for the development of novel drugs, especially for orphan GPCRs for which endogenous ligands are unknown. One of the orphan GPCR subfamilies, Super conserved Receptor Expressed in Brain (SREB), consists of GPR27, GPR85 and GPR173 and is expressed in the central nervous system. We report herein the identification of inverse agonists for the SREB family without their agonists. We carried out an in vitro screening of 5472 chemical compounds from the RIKEN NPDepo chemical library. The binding of [ 35 S]GTPγS to the GPR173–Gsα fusion protein expressed in Sf9 cells was measured and resulted in the identification of 8 novel GPR173 inverse agonists. The most potent compound showed an IC50 of approximately 8 μm . The identified compounds were also antagonists for other SREB members, GPR27 and GPR85. These results indicated that the SREB family could couple Gs‐type G proteins, and SREB–Gsα fusion proteins showed significant constitutive activities. Moreover, a molecular model of GPR173 was constructed using the screening results. The combination of computational and biological methods will provide a unique approach to ligand identification for orphan GPCRs and brain research. Abstract : One of the orphan GPCR subfamilies, Super conserved Receptor Expressed in Brain (SREB), consists of GPR27, GPR85 and GPR173 and is expressed in the central nervous system. We report the identification of inverse agonists for the SREB family without their agonists.